2015
DOI: 10.15664/jtr.1184
|View full text |Cite
|
Sign up to set email alerts
|

A Social Identity and Social Power Perspective on Terrorism

Abstract: This article presents a theoretical framework for understanding terrorism that is grounded in experimental work on social identity and social power. It is suggested that social identity salience and social power may be harnessed to reduce terrorist activity by reducing perceptions of threat from the view of terrorist organizations, by reducing perceived threat of terrorist activity from the view of potential targets, and by addressing distributions of and susceptibility to social power as it relates to accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Consistent with our hypothesis and previous studies (van Zomeren, Postmes, & Spears, ; J. D. Wright, ), we found that social identity significantly predicted support for Islamist terrorism. We found this association in all stages of the analysis that we performed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our hypothesis and previous studies (van Zomeren, Postmes, & Spears, ; J. D. Wright, ), we found that social identity significantly predicted support for Islamist terrorism. We found this association in all stages of the analysis that we performed.…”
Section: Discussionsupporting
confidence: 92%
“…This argument is based on previous studies which have indicated that terrorism is mainly driven by social identity. One of the main reasons for social identity driving terrorism is identity being under threat (Putra & Sukabdi, ; Schwartz, Dunkel, & Waterman, ; Taylor & Louis, ; J. D. Wright, ). The basic idea is that when people perceive that their identity is threatened, their self‐esteem also is being threatened.…”
Section: Introductionmentioning
confidence: 99%
“…Accompanying this public concern, terrorist motivations have received both popular (e.g., Siddique, ) and scholarly (e.g., Singh, Vatsa, & Noor, ) attention. Empirical efforts have offered several drives for terrorist behavior, such as a quest for significance (i.e., becoming “immortalized;” Kruglanski, Chen, Dechesne, Fishman, & Orehek, ) and strong group identification (Ginges & Atran, ; Wright, ). Though valuable, these contributions are limited in their explanatory scope, focusing on singular reasons for terrorism (e.g., a quest for significance, group identity) or single types of terrorism (e.g., suicidal bombings; Kruglanski et al, ).…”
Section: Research On Terrorist Groups’ Motivationsmentioning
confidence: 99%
“…Despite any natural aversions to heinous acts such as murder, individuals may view murder as morally justified if they perceive that they are working toward the greater good, such as eliminating threats to society (Wright, ) or combatting presumable political unfairness/deprivation (Moghaddam, ). As Coady () remarks, the distinction between the revolutionary action of freedom fighters and terrorism toward noncombatants is subjective, as many terrorists consider their actions to be in line with the former.…”
Section: Research On Terrorist Groups’ Motivationsmentioning
confidence: 99%
“…The terrorism of the 21 st century involves ‘intelligent and motivated opponent[s]’ (Slovic & Weber, :2) who target civilians indiscriminately. This not only makes prediction more challenging, it can elevate irrational and exaggerated fear (Wright, ) in the minds of potential travellers. Because the event is unknown, the outcome cannot be predicted (Sayer, ; Yeung, ; De Roo, Hillier, & Van Wezemael, ).…”
Section: Terrorism Intergroup Conflict and Fearmentioning
confidence: 99%